Polymethoxyflavones from Gardenia oudiepe (Rubiaceae) induce cytoskeleton disruption-mediated apoptosis and sensitize BRAF-mutated melanoma cells to chemotherapy. (1st July 2020) - Gonçalves de Oliveira-Júnior, Raimundo; Marcoult-Fréville, Nolwenn; Prunier, Grégoire; Beaugeard, Laureen; Beserra de Alencar Filho, Edilson; Simões Mourão, Eduard David; Michel, Sylvie; Quintans-Júnior, Lucindo José; Guedes da Silva Almeida, Jackson Roberto; Grougnet, Raphaël; Picot, Laurent
Abstract: A series of 10 natural and semisynthetic flavonoids (1 to 10 ) were obtained from Gardenia oudiepe (Rubiaceae), an endemic plant from New Caledonia. Most of them were polymethoxylated flavones (PMFs) of rare occurrence. After a cell viability screening test, PMFs 2 and 3 showed significant cytotoxic activity against A2058 human melanoma cells (IC50  = 3.92 and 8.18 μM, respectively) and were selected for in-depth pharmacological assays. Both compounds inhibited cell migration and induced apoptosis and cell cycle arrest after 72h of treatment. Immunofluorescence assays indicated that these outcomes were possibly related to the induction of cytoskeleton disruption associated to actin and tubulin depolymerization. These data were confirmed by molecular docking studies, which showed a good interaction between PMFs 2 and 3 and tubulin, particularly at the colchicine binding site. As A2058 are considered as chemoresistant to conventional chemotherapy, compounds 2 and 3 (½IC50 ) were associated to clinically-used antimelanoma drugs (vemurafenib and dacarbazine) and combined therapies efficacy was assessed by the MTT assay. PMFs 2 restored the sensitivity of A2058 cells to dacarbazine treatment (IC50  = 49.38 μM vs. >100 μM). Taken together, these data suggest that PMFs from G. oudiepe could be potential leaders for the design of new antimelanoma drugs. Graphical abstract: Image 1 Highlights: PMFs from G. oudiepe inhibited proliferation and migration of A2058 cells. PMFs 2 and 3 induced apoptosis, cell cycle arrest and cytoskeleton disruption. Molecular docking showed a good interaction of PMFs on the colchicine binding site. PMF 2 sensitized melanoma cells to dacarbazine.